Aspectos farmacológicos e sociodemográficos associados à injúria renal precoce em idosos atendidos no ambulatório de geriatria de um hospital universitário - Alves, Hérick Hebert da Silva (2023)
Elderly individuals over 60 years of age are the most frequent carriers of kidney disease, therefore, the presence of chronic diseases associated with aging, polypharmacy and decline in renal function are considered. The objective of the study was to investigate the sociodemographic profiles, drug therapy and laboratory data in elderly outpatients. This is a cross-sectional, descriptive, explanatory study consisting of a qualitative and quantitative approach. It was carried out at the Geriatrics Service of the Walter Cantídio University Hospital/Ebserh with elderly individuals aged 60 to 80 years who opened for care between July 2021 and October 2022. A specific questionnaire was used to collect data to search for the sociodemographic profile, laboratory tests, medications used and the presence of data from the Mini Mental State Examination. The research was approved by the ethics committee CAAE 36199620.5.0000.5054 of the aforementioned institutions. To obtain the data, a total of 130 medical records were analyzed and, after comparing them with the inclusion and exclusion criteria, the final sample consisted of 66 participants. The majority were female, aged between 60 and 69 years. The average obtained by applying the MMSE was 25.9 points, resulting in good cognitive performance for schooling. Among the most prescribed classes for the elderly in this study were antilipemic drugs (40.9%), followed by antidiabetic drugs (37.9%) and diuretics. A considerable prevalence of obesity and underweight was found. Regarding laboratory tests and assessment of renal function of the elderly studied, it was observed that there was a scarce request for tests for classic markers such as urea and creatinine. All the elderly in this study are polymedicated and many of these drugs can somehow interfere with laboratory results, especially renal biomarkers, when not informed before collection and contribute to the progression of the disease. Therefore, this research corroborated with important data to identify the lack of information and the factors associated with kidney injury that will serve as a basis for the development of protocols for assistance to the elderly and subsidies for the proposal of public policies.